A Callixylon (Archaeopteridales, Progymnospermopsida) trunk with preserved secondary phloem from the Late Devonian of Morocco1. Issue 11 (1st November 2013) - Decombeix, Anne‐Laure; Meyer‐Berthaud, Brigitte
Abstract : Premise of the study: During the Devonian, the evolution of secondary phloem produced by a bifacial vascular cambium was a key innovation that increased the ability of plants within the lignophyte clade to redistribute photosynthates and other organic compounds throughout their body. Unraveling the secondary phloem anatomy of the first arborescent lignophytes is crucial to understand the evolution of this tissue and the physiology of early trees. Methods: A 10 cm wide stem of Callixylon with preserved secondary phloem from the Famennian of Morocco is described using thin‐sections. Key results: The secondary phloem of this Callixylon zalesskyi ‐type of stem is composed of fibers, sclereids, rays, axial parenchyma, and putative sieve cells. Fibers differentiate early and are relatively abundant in the inner phloem. In the older phloem, fibers are arranged in tangential bands alternating with extensive layers of axial parenchyma. Changes between the young and old phloem involve the periclinal division and radial elongation of the axial parenchyma cells. The presence of fibers in the inner, presumably functional phloem, combined with evidence for rhythmicity in the production of different phloem cell types are documented for the first time in detail in an archaeopteridalean progymnosperm. No periderm was observed within the preserved seven millimeters of bark tissues. Conclusions: The secondary phloem anatomy supports a close affinity of archaeopteridalean progymnosperms with both aneurophytalean progymnosperms and seed plants. The production of secondary phloem might have provided an advantage to these first arborescent lignophytes over other types of Devonian early trees, especially in dry conditions.